2009
DOI: 10.1080/02713680802542053
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Engineered Elastin-Like Polymer as a Substratum to Culture Cells from the Ocular Surface

Abstract: The recombinant ELP resembling the ocular surface extracellular matrix was a suitable substratum to sustain epithelial cell attachment and growth. This type of polymer may be suitable for tissue engineering to restore vision by reconstructing the ocular surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…Indeed, others have found that ELR containing RGD either caused an increase in initial cell adhesion (bone marrow stem cells [4], SaOS-2 [20]) or in both epithelial cell adhesion and proliferation [5]. The mechanism by which the ELR shows its effect is worth investigating for both tissue engineering and regenerative medicine applications and for fundamental research on epithelial disorders such as carcinogenesis.…”
Section: Immunohistochemistrymentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, others have found that ELR containing RGD either caused an increase in initial cell adhesion (bone marrow stem cells [4], SaOS-2 [20]) or in both epithelial cell adhesion and proliferation [5]. The mechanism by which the ELR shows its effect is worth investigating for both tissue engineering and regenerative medicine applications and for fundamental research on epithelial disorders such as carcinogenesis.…”
Section: Immunohistochemistrymentioning
confidence: 97%
“…The first ELR products were simple peptides, to which the cells did not attach. Soon after, they were enriched with short peptide sequences having specific bioactivity [3] and have been used as coatings [4], films [5] for improved cell attachment, and as hydrogels to promote chondrogenesis [6].…”
Section: Introductionmentioning
confidence: 99%
“…This type of polymer may therefore be suitable for tissue engineering to restore vision by reconstructing the ocular surface. One of the potential applications we envision for this kind of protein-based polymer is the preparation of scaffolds to be used for ocular surface tissue engineering [45].…”
Section: Elrsmentioning
confidence: 99%
“…Highly porous hydrogels have been conceived by chemical cross-linking of ELRs containing REDV sequence: salt leaching/gas foaming was performed to obtain suitable 3D scaffolds promoting infiltration of HUVEC cells inside the porous network ( Figure 5.4) [133]. Another potential application of these bioactive ELRs is the preparation of films to be used for ocular surface tissue engineering [134,135]. Recently, Srivastava et al [135] have successfully investigated the use of ELRs as a substrate to maintain the growth, phenotype, and functional characteristics of retinal pigment epithelial cells in vitro to obtain a suitable carrier for transplantation in the treatment of age-related macular degeneration.…”
Section: Tissue Engineeringmentioning
confidence: 99%